Data modeling for inter- and intra-individual stability of young swimmers` performance: A longitudinal cluster analysis - Morais, J. E.; Forte, P.; Silva, A. J.; Barbosa, T. M.; Marinho, D. A. (Research Quarterly for Exercise and Sport, 2021)
Purpose: The aims of this study were to classify, identify and follow-up young swimmers` performance and its biomechanical determinants during two competitive seasons (in seven different moments of assessment—M), and analyze the individual variations of each swimmer. Method: Thirty young swimmers (14 boys: 12.70 ± 0.63 years-old; 16 girls: 11.72 ± 0.71 years-old) were recruited. A set of anthropometric, kinematic, efficiency, hydrodynamic and mechanical power variables were assessed. Results: The cluster solution (i.e., number of ideal clusters for this sample) resulted in three clusters, which were named as: cluster 1 ("talented"), cluster 2 ("proficient"), and cluster 3 ("non-proficient"). The performance improved between moments of assessment in all clusters (cluster 1—M1: 68.07 ± 6.62s vs M7: 61.46 ± 3.43s; cluster 2—M1: 73.14 ± 4.87s vs M7: 65.33 ± 2.97s; cluster 3—M1: 82.60 ± 4.18s vs M7: 70.09 ± 3.48s). Anthropometric features also increased between moments of assessment, and remaining biomechanical variables (kinematic, efficiency, hydrodynamic and mechanical power) also increased between M1 and M7, in all clusters. Cluster 1 increased their swimmer`s membership between M1 and M7 (4 to 11), cluster 2 decreased (12 to 5), and cluster 3 maintained (14). Conclusion: It can be concluded that the cluster formation depends on different determinant factors during two competitive seasons, and young swimmers are prone to change from one cluster to another over this period of time.